Identifikation von Schlüsselberufen der Transformation auf Basis der EU-Taxonomie - Finn Arnd Wendland (Institut der deutschen Wirtschaft (IW), 2022)
Der Arbeitsmarkt ist im Zuge der klimapolitischen Herausforderungen einem erheblichen Transformationsdruck ausgesetzt. Während bestimmte Fähigkeiten und Kompetenzen auf dem Weg zu einer klimaneutralen Wertschöpfung an Bedeutung gewinnen (sogenannte Green Jobs), gibt es andere, die absehbar an Bedeutung verlieren. Damit Politik, Unternehmen und Arbeitnehmer diese Entwicklung frühzeitig antizipieren können, ist das Wissen über den Wandel beruflicher Anforderungen vor dem Hintergrund der Dekarbonisierung von hoher Relevanz. Ob zur Steuerung der Arbeits- und Bildungspolitik, zur Planung von Unternehmensstrategien oder für die Perspektive von Beschäftigten in betroffenen Branchen: Die Kenntnis über künftige Fachkräftebedarfe hilft, Fachkräfteengpässe und sozialen Spannungen vorzubeugen und ist zentral für das Gelingen der Transformation. [...] – – The economic transformation to carbon neutrality increasingly produces various forms of pressures in different job areas and on the labour market, especially in energy- and emission-intensive manufacturing industries. As new technologies are implemented and new tasks emerge, employers also require new skills and qualifications from their employees. While decarbonisation can be associated with overall positive employment outcomes according to various studies, temporal and spatial mismatches as well as unequal sectoral dynamics imply varying consequences for each employee individually. This study examines the degree to which different job areas and occupational groups are likely to be affected from transformative dynamics of decarbonisation in the manufacturing sector. The methodology is based on the EU taxonomy, which targets key manufacturing sectors for industrial adaptation and change, i.e. energy-intensive basic material industries and lead markets for the provision of climate-neutral technologies. Based on the distribution of occupational groups by sectors and employment aggregates, the studies shows that production-oriented jobs (in contrast to service-oriented jobs) are particularly exposed to decarbonisation pressures in taxonomy-relevant industries. Identified key occupations share a high exposure to transformation pressures through involvement in either Enabling- or "Green"/ Transition activities. The exposure matrix elaborated provides new starting points to analysis employment dynamics from a macro-perspective.
Keywords: 330